2018
DOI: 10.1186/s12885-017-3912-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cancer incidence in Australian farm residents 45 years and over, compared to rural non-farm and urban residents - a data linkage study

Abstract: BackgroundIt is not known if the incidence of common cancers in Australian farm residents is different to rural non-farm or urban residents.MethodsData from farm, rural non-farm and urban participants of the 45 and Up Study cohort in New South Wales, Australia, were linked with state cancer registry data for the years 2006–2009. Directly standardised rate ratios for cancer incidence were compared for all-cancer, prostate, breast, colorectal cancer, melanoma and non-Hodgkin Lymphoma (NHL). Proportional hazards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…While eight of the USA-based studies, reported higher incidence rates among urban residents (or those from areas with higher density of urologists) (25, 38, 40–44, 46), two found no geographical differentials (39, 45). Similarly, two Australian studies reported no significant differences (31, 54), three studies found higher prostate cancer incidence among urban males (32, 52, 53) and one study recorded the reverse pattern (55). In Denmark, urban men had higher incidence rates from 1994 to 2003 (47), but no differential was evident from 2004 to 2008 (48).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…While eight of the USA-based studies, reported higher incidence rates among urban residents (or those from areas with higher density of urologists) (25, 38, 40–44, 46), two found no geographical differentials (39, 45). Similarly, two Australian studies reported no significant differences (31, 54), three studies found higher prostate cancer incidence among urban males (32, 52, 53) and one study recorded the reverse pattern (55). In Denmark, urban men had higher incidence rates from 1994 to 2003 (47), but no differential was evident from 2004 to 2008 (48).…”
Section: Resultsmentioning
confidence: 95%
“…Of the 23 studies included, 14 (six high, eight moderate quality) reported higher prostate cancer incidence rates in urban areas (25, 32, 36, 38, 40–44, 46, 47, 49, 52, 53), two (moderate) higher rates in rural areas (50, 55) and seven (one high, six moderate) no urban rural differences (31, 37, 39, 45, 48, 51, 54) (Figure 2; Table 3). Six studies used a mixture of data collected both prior to and after the widespread use of PSA testing, which combined with varying time-periods for analysis, could lead to conflicting patterns (31, 32, 39, 49, 51, 55).…”
Section: Resultsmentioning
confidence: 99%